2020
DOI: 10.1112/mtk.12059
|View full text |Cite
|
Sign up to set email alerts
|

Envy‐free Division Using Mapping Degree

Abstract: In this paper we study envy‐free division problems. The classical approach to such problems, used by David Gale, reduces to considering continuous maps of a simplex to itself and finding sufficient conditions for this map to hit the center of the simplex. The mere continuity of the map is not sufficient for reaching such a conclusion. Classically, one makes additional assumptions on the behavior of the map on the boundary of the simplex (e.g., in the Knaster–Kuratowski–Mazurkiewicz and the Gale theorem). We fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Let us comment briefly the special case when m = 1. Since the agents might prefer zero-length pieces in our setting, our theorem boils down then to a recent result of Avvakumov and Karasev [2]. They showed that when n is a prime power, there always exists an envy-free division, even if we do not assume that the agents are hungry, but that this is not true anymore if n is not a prime power.…”
Section: Preliminariesmentioning
confidence: 71%
See 3 more Smart Citations
“…Let us comment briefly the special case when m = 1. Since the agents might prefer zero-length pieces in our setting, our theorem boils down then to a recent result of Avvakumov and Karasev [2]. They showed that when n is a prime power, there always exists an envy-free division, even if we do not assume that the agents are hungry, but that this is not true anymore if n is not a prime power.…”
Section: Preliminariesmentioning
confidence: 71%
“…Here, some agents may find that a part of the cake is unappetizing and prefer nothing, while others may find it tasty. Even in such cases, an envy-free division only using n − 1 cuts has been shown to exist for a particular number n of agents under the assumption of closed preferences [2,14,15,16]. The most general result obtained so far is the one by Avvakumov and Karasev [2], who showed the existence of an envy-free division for the case when n is a prime power.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Many variations of the cake-splitting problem have been studied [Wel85, BT96, Bar05, Pro15] , including partitions of multiple cakes or pieces per participant [CNS10, NSZ20, ABB + 20, SH21], partitions with secretive guests [AFP + 18], and partitions weakening the hungry condition if there are empty pieces [MZ19,AK21].…”
Section: Introductionmentioning
confidence: 99%